Serializing the Past in and out of the Leisure Hour: Historical Culture and the Negotiation of Media Boundaries - Lechner, Doris (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2013)
This article explores the media transfer between books and periodicals by example of historical narratives serialized within the Religious Tract Society’s family magazine Leisure Hour (1852-1905). A look at the travelling of texts and ideas between these two media shows that the RTS not only negotiated media boundaries but operated at the intersection of other categories, such as class and gender, linked to the reputation of the different media as well as modes of representation and approaches to history. In a combination of book history and periodical studies under a historical culture perspective, the article focuses on three case studies: (1) the transition from book into periodical serial and the (re)appropriation of history for a working-class audience; (2) the collection of a periodical series into book form and the author’s boundary-work under the regulation of the RTS; (3) the transfer of material features in the creation of monthly parts and shift in historical genre.